2018
DOI: 10.1111/joim.12747
|View full text |Cite
|
Sign up to set email alerts
|

The role of pregnancy, perinatal factors and hormones in maternal cancer risk: a review of the evidence

Abstract: An understanding of the origin of cancer is critical for cancer prevention and treatment. Complex biological mechanisms promote carcinogenesis, and there is increasing evidence that pregnancy‐related exposures influence foetal growth cell division and organ functioning and may have a long‐lasting impact on health and disease susceptibility in the mothers and offspring. Nulliparity is an established risk factor for breast, ovarian, endometrial and possibly pancreatic cancer, whilst the risk of kidney cancer is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 132 publications
(169 reference statements)
2
90
0
5
Order By: Relevance
“…15–23). Some of these studies reported that increased parity also reduced the risk for endometrial and ovarian cancers . For women with five or more children a 50% reduction in breast cancer risk has been reported .…”
Section: Breast Cancer Risk Of Multiparous Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…15–23). Some of these studies reported that increased parity also reduced the risk for endometrial and ovarian cancers . For women with five or more children a 50% reduction in breast cancer risk has been reported .…”
Section: Breast Cancer Risk Of Multiparous Womenmentioning
confidence: 99%
“…Risk reduction for breast cancers after several deliveries and breast-feeding periods has been described for several decades (reviewed in Refs. [15][16][17][18][19][20][21][22][23]. Some of these studies reported that increased parity also reduced the risk for endometrial and ovarian cancers.…”
Section: Breast Cancer Risk Of Multiparous Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of socioeconomic changes and unique reproductive patterns, breast carcinoma has become one of the most extensively increasing cancers in China . Despite advances in surgical techniques and improved understanding of carcinogenesis, the prognosis for patients is still suboptimal, especially in developing countries. General risk factors of breast cancer in women include age, infertility, inherited changes in certain genes, high levels of certain hormones and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In female humans, ovarian epithelial cancer is one of the most prevalent and lethal gynecologic malignancies, and the cell of origin is likely a transformed oviduct fimbrial epithelial cell (Kindelberger et al, 2007;Siegel et al, 2016). Further, a decrease in the number of ovulationseither through pregnancy and lactation, or hormonal contraception -is correlated with a decrease in the risk of ovarian epithelial cancer (Hankinson et al, 1992;Purdie et al, 2003;Tung et al, 2005;Kindelberger et al, 2007;Havrilesky et al, 2013;Troisi et al, 2018). Therefore, recurrent exposure to ovulatory fluid is damaging to oviduct epithelial cells, which increases the risk of ovarian epithelial cancer.…”
Section: Trachea Mccsmentioning
confidence: 99%